Scoliosis in rhythmic gymnasts - Tanchev, P. I.; Dzherov, A. D.; Parushev, A. D.; Dikov, D. M.; Todorov, M. B. (Spine, 2000)
STUDY DESIGN: An anamnestic, clinical, radiographic study of 100 girls actively engaged in rhythmic gymnastics was performed in an attempt to explain the higher incidence and the specific features of scoliosis in rhythmic gymnastic trainees. OBJECTIVES: To analyze the anthropometry, the regimen of motion and dieting, the specificity of training in rhythmic gymnastics, and the growth and maturing of the trainees, and to outline the characteristics of the scoliotic curves observed. An etiologic hypothesis for this specific subgroup of scoliosis is proposed. SUMMARY OF BACKGROUND DATA: The etiology of scoliosis remains unknown in most cases despite extensive research. In the current classifications, no separate type of sports-associated scoliosis is suggested. METHODS: The examinations included anamnesis, weight and height measurements, growth and maturing data, eating regimen, general and back status, duration, intensity, and specific elements of rhythmic gymnastic training. Radiographs were taken in all the patients with suspected scoliosis. The results obtained were compared with the parameters of normal girls not involved in sports. RESULTS: A 10-fold higher incidence of scoliosis was found in rhythmic gymnastic trainees (12%) than in their normal coevals (1.1%). Delay in menarche and generalized joint laxity are common in rhythmic gymnastic trainees. The authors observed a significant physical loading with the persistently repeated asymmetric stress on the growing spine associated with the nature of rhythmic gymnastics. Some specific features of scoliosis related to rhythmic gymnastics were found also. CONCLUSIONS: This study identified a separate scoliotic entity associated with rhythmic gymnastics. The results strongly suggest the important etiologic role of a "dangerous triad": generalized joint laxity, delayed maturity, and asymmetric spinal loading.